Apolipoprotein L1 Gene Variants in Deceased Organ Donors Are Associated With Renal Allograft Failure. Issue 6 (24th March 2015) - Freedman, B. I.; Julian, B. A.; Pastan, S. O.; Israni, A. K.; Schladt, D.; Gautreaux, M. D.; Hauptfeld, V.; Bray, R. A.; Gebel, H. M.; Kirk, A. D.; Gaston, R. S.; Rogers, J.; et al.
<x xml:space="preserve">Abstract</x> Apolipoprotein L1 gene (APOL1) nephropathy variants in African American deceased kidney donors were associated with shorter renal allograft survival in a prior single‐center report. APOL1 G1 and G2 variants were genotyped in newly accrued DNA samples from African American deceased donors of kidneys recovered and/or transplanted in Alabama and North Carolina. APOL1 genotypes and allograft outcomes in subsequent transplants from 55 U.S. centers were linked, adjusting for age, sex and race/ethnicity of recipients, HLA match, cold ischemia time, panel reactive antibody levels, and donor type. For 221 transplantations from kidneys recovered in Alabama, there was a statistical trend toward shorter allograft survival in recipients of two‐APOL1‐nephropathy‐variant kidneys (hazard ratio [HR] 2.71; p = 0.06). For all 675 kidneys transplanted from donors at both centers, APOL1 genotype (HR 2.26; p = 0.001) and African American recipient race/ethnicity (HR 1.60; p = 0.03) were associated with allograft failure. Kidneys from African American deceased donors with two APOL1 nephropathy variants reproducibly associate with higher risk for allograft failure after transplantation. These findings warrant consideration of rapidly genotyping deceased African American kidney donors for APOL1 risk variants at organ recovery and incorporation of results into allocation and informed‐consent processes.